IMPROVING THE AUDIT OF FIXED EQUIPMENT IN NON-STATE NON-PROFIT ORGANIZATIONS - Khojiyev Mekhriddin Sulaymonovich , (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
In this article, problems related to the organization and improvement of the audit of fixed assets in non-state non-profit organizations are studied and scientific and practical suggestions are highlighted. This, in turn, will be the basis for providing the founders with an audit report based on the final results of the audit in order to improve the audit of fixed assets of non-state non-profit organizations (NSNPOs) in order to give an objective and truthful assessment of the work activities of the executive director and chief accountant and the heads of the relevant department in accordance with the normative documents.